Assessing and Developing Primary Education Curricula Based on Bloom’s Taxonomy: A Reconciliatory Approach - Nur Hafizah, Elma; Sigit Prasetyo (ATTA`DIB, 2026)
Curriculum changes in Indonesia, from the pre-KTSP era to the Independent Curriculum, indicate a paradigm shift from a rote-based approach to student-centered learning. While aimed at improving critical thinking skills, these changes have raised concerns regarding a decline in academic competitiveness and depth of conceptual mastery. This study aims to encourage the dynamics of assessment and curriculum development at the elementary education level by promoting a reconciliation model through the consistent application of Bloom's Taxonomy. Using the Systematic Literature Review (SLR) method following the PRISMA protocol, 35 relevant articles from national and international baseline data (2015–2025) were analyzed in depth.  The review results indicate that the majority of studies (88.6%) used a qualitative approach. Key findings revealed inconsistencies in the integration of all cognitive levels of Bloom's Taxonomy (C1–C6) in existing assessment instruments. Most assessment practices still tend to focus on lower cognitive domains, thus not explicitly and systematically measuring higher-order thinking skills (HRT) in a comprehensive manner. Furthermore, significant challenges were identified for teachers in implementing an integrated curriculum without sacrificing deep knowledge structures.  The implications of this research offer a "middle ground" model that integrates the advantages of discipline-based and integrated curricula through the implementation of Bloom's Taxonomy in a tiered and proportionate manner, tailored to the developmental stages of elementary school students. The article's scientific contribution lies in the formulation of an operational framework that balances thematic flexibility with a systematic knowledge structure to improve the quality of learning and assessment in elementary schools.